Methodological Issues of Application of Process Costing of Product Costing - Dilfuza Toshnazarova (International Journal on Integrated Education, 2022)
This article proves that the development of a methodical procedure for calculating the cost of products according to international standards is an urgent issue for the enterprises of our country. The article analyzes the literature on the application of process costing. Based on the study of foreign experiences, based on the practical materials of enterprises operating in our country, the procedure for calculating the equivalent unit of products in process costing is presented. A five-step methodological approach to process costing using FIFO and weighted average methods is illustrated in practical examples. The results of FIFO and weighted average method are compared and the reasons for the differences are analyzed. The application of these methodological approaches based on advanced foreign experiences in the practice of enterprises serves to form reliable information about the cost of products.